Estuary-dependency and multiple habitat connectivity of juvenile leervis lichia amia (pisces: carangidae) and the factors influencing their movements - Murray, Taryn Sara (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Estuaries are highly productive ecosystems that provide an important nursery function to many marine-spawning fish species. While in estuaries, the juveniles of estuary-associated fishes are exposed to frequent, abrupt changes in environmental conditions and, as such, utilise movement as a strategy to cope with the changing conditions. Therefore, to gain a better understanding of the importance of estuaries (i.e. estuary-dependency) to estuary-associated species, knowledge on their movement patterns within estuaries, the links between habitats, and the environmental and cyclical processes driving these movements, is necessary. Lichia amia, commonly known as leervis or garrick in southern Africa, is an over-exploited, estuary-dependent fishery species targeted by coastal recreational and subsistence fishers, as well as spearfishers, throughout its South African distribution. Aspects of its biology and life history have been assessed; however, knowledge on its movement behaviour is limited to a single conventional dart tagging study, which described large-scale coastal movements of juvenile, sub-adult and adult leervis. As such, little is known about area use and movement patterns within estuaries, or the degree of connectivity between estuarine and marine habitats. Therefore, the aim of this study, using conventional dart tagging and passive acoustic telemetry methods, was to assess the role of estuarine nursery habitats in the life cycle of the leervis by examining area use patterns and movement behaviour within estuaries, investigating the degree of habitat connectivity, and determining the drivers (cyclical rhythms and environmental variables) of estuarine use and connectivity. A dedicated conventional mark-recapture study on juvenile leervis within the Swartkops Estuary revealed a high level of estuarine fidelity (philopatry) suggesting that estuaries are important nursery habitats. However, movement distances increased with increasing fish length, with some fish also being recaptured in the neighbouring marine environment. These results provided evidence of an ontogenetic habitat shift, with smaller fish remaining in the estuary for extended periods and larger individuals undertaking more extensive movements. Complementary passive acoustic telemetry studies were conducted in the Kowie and Goukou estuaries, spaced 620 km apart, to assess area use, movement patterns, residency and multiple habitat connectivity of juvenile leervis. These telemetry studies showed varying levels of residency within the tagging estuaries, and seasonal variation in area use. The lengths of estuary used by leervis tagged in the Kowie Estuary generally decreased with the onset of austral winter, while fish tagged in the Goukou Estuary generally moved into the marine environment. Despite tagged individuals spending on average 56% and 38% of the total monitoring periods within the Kowie and Goukou estuaries, respectively, fish displayed high levels of multiple habitat connectivity, with 71% and 76% of Kowie and Goukou fish, respectively, visiting adjacent marine and estuarine environments. A total of 11 different neighbouring habitats (estuaries and ports) were visited by Kowie fish, while fish tagged in the Goukou Estuary only visited four adjacent habitats. These differences in connectivity could be attributed to the proximity of many more estuaries to the Kowie Estuary compared to the Goukou Estuary. Estuarine movements by acoustically tagged leervis in both estuaries followed a strong diel but a much weaker tidal pattern. A number of environmental variables significantly influenced estuarine movements and marine excursions (including river inflow, photoperiod and moon phase). However, water temperature (river and sea) had the most significant effects on these movements, with decreasing winter river temperatures coincident with a downstream shift in mean daily position of fish tagged in the Kowie Estuary, and movement into the marine environment from the Goukou Estuary. Interestingly, the area use patterns of juvenile leervis tagged in the Kowie and Goukou estuaries were different, predominantly using limited portions of each estuary. Kowie fish spent more time in the mouth region and lower reaches, while Goukou fish spent more time in the lower and middle reaches of the estuary. Therefore, should no-take Estuarine Protected Areas be implemented, inter-estuary differences would need to be considered to determine the most effective stretches of estuary to close to provide maximum protection for leervis. This study provided new information on the movement behaviour of juvenile leervis, the degree to which juveniles depend on estuaries as nursery areas, and the cyclical rhythms and environmental factors influencing their movements. The study therefore contributes considerably to our understanding of the role of estuaries in the life history of leervis, and provides essential information for the improved management of this over-exploited species.
Keywords: Uncatalogued